PENGEMBANGAN MEDIA KARIER BERBASIS WEBSITE UNTUK MENINGKATKAN PERENCANAAN KARIER SISWA SMP TINGKAT VIII - Hariyani, Endah; Rukanda, Nandang; Irmayanti, Rima (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2023)
Careeruis a formoof individualuself-ability thatais implementedein histlife in order to achieve the goalseiof achievement that havenbeen setdduring his life because careertsuccess indthe present is one of society'stbenchmarks forethe successlof andindividual who respects himself more because he has achieved the desired career satisfaction. according to a predetermined plan. The purpose of this study is to find out the process of developing a website-based career media to improve career planning for junior high school students level VIII. This confirms that the right media is needed to support students in improving career planning. The research method used is Research and Development (R&D) which aims to develop products in the form of website-based career media. The researcher's data collection technique used observation sheets, validation and questionnaires. In this study the authors used a population of class VIII students totaling 35 people to be tested. The results showed that the Development of Website-Based Career Media to Improve Career Planning for Level VIII Students of SMP Negeri 2 Batujajar showed a feasibility level of 76% and said "Decent". Calculated in parallel from of MediasExpert Test with an average of 78%, the resultsyof the FeasibilityoTest of the Material Expert with an average of 62%, the results of the FeasibilityoTest of the Product Material of the Practitioner respondents withean averagesof 88%, and the results of the Feasibility Testuof the ProductiMaterial of thedstudent response with an average of 85.1%. Stating that in general the development of website-based career media has feasibility in the high category.